Isolation and molecular detection of Avipoxvirus from field outbreaks in Mymensingh, Bangladesh - Rahman, Saifur; Islam, Md Ariful; Islam, Md Shafiqul; Nazir, KHM Nazmul Hussain; Khan, Md Shahidur Rahman (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The present study was performed for isolation, identification, and molecular detection of Avipoxvirus [Turkeypox virus (TPV), Fowlpox virus (FPV), and Pigeonpox virus (PPV)] from field outbreaks in some selected areas of Mymensingh division, Bangladesh. Materials and Methods: A total of 60 suspected cutaneous nodular samples (10 TPV, 20 PPV, and 30 FPV) were collected. The samples were then subjected to isolation and identification by chicken embryo propagation followed by confirmation using polymerase chain reaction (PCR). Results: The TPV, FPV, and PPV were successfully isolated and identified from the nodular samples using embryo propagation and PCR technique targeting pox virus p4b gene. Out of 10 Turkeypox suspected field samples, five (50%) were positive for TPV. Similarly, among 30 Fowl pox suspected field samples, 12 (40%), and out of 20 Pigeonpox suspected field samples, eight (40%) were found to be positive for FPV and PPV, respectively. The overall prevalence of avipox (TPV, FPV, and PPV) virus infections in Mymensingh division was 41.67% (n = 25/60). Conclusion: This study has shown that TPV, FPV, and PPV are circulating in Mymensingh division. The isolated TPV, FPV, and PPV field isolates can be used as vaccine candidates to develop an effective vaccine for effective controlling of the avipox in Mymensingh division and surrounding areas. J. Adv. Vet. Anim. Res., 6(1): 54-59, March 2019